COVID-19 living evidence profile #1 (version 1.3): What is known about anticipated COVID-19 vaccine roll-out elements? - Wilson, MG; Bain, T; Wang, Q; Al-Khateeb, S; Bhuiya, AR; Alam, S; DeMaio, P; Gauvin, François-Pierre; Ahmad, A; Drakos, A; Sharma, K; Whitelaw, S; et al. (My University, 2021)
An overview of the best available research evidence from around the world (i.e., evidence syntheses) and local research evidence (i.e., single studies) and, if applicable, a scan of experiences from other countries and from Canadian provinces and territories, about anticipated COVID-19 vaccine roll-out elements in response to a decision-maker’s request.
Keywords: COVID-19; vaccine; roll-out